2008
DOI: 10.1242/dev.021121
|View full text |Cite
|
Sign up to set email alerts
|

Defining early lineage specification of human embryonic stem cells by the orchestrated balance of canonical Wnt/β-catenin, Activin/Nodal and BMP signaling

Abstract: The canonical Wnt/β-catenin signaling has remarkably diverse roles in embryonic development, stem cell self-renewal and cancer progression. Here, we show that stabilized expression of β-catenin perturbed human embryonic stem (hES)-cell self-renewal, such that up to 80% of the hES cells developed into the primitive streak (PS)/mesoderm progenitors, reminiscent of early mammalian embryogenesis. The formation of the PS/mesoderm progenitors essentially depended on the cooperative action of β-catenin together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
242
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(263 citation statements)
references
References 47 publications
17
242
2
2
Order By: Relevance
“…Interestingly, it has been reported that BMP, Wnt and NODAL can regulate each other and form a signaling loop essential for early lineage specification of mouse and human embryonic stem cells [60][61][62]. In this study we have shown that MSX2 acts as a direct target gene of BMP4, while Wnt signaling activates MSX2 expression synergistically with BMP.…”
Section: Nodal Signaling Is An Essential Downstream Effector Of Msx2supporting
confidence: 50%
“…Interestingly, it has been reported that BMP, Wnt and NODAL can regulate each other and form a signaling loop essential for early lineage specification of mouse and human embryonic stem cells [60][61][62]. In this study we have shown that MSX2 acts as a direct target gene of BMP4, while Wnt signaling activates MSX2 expression synergistically with BMP.…”
Section: Nodal Signaling Is An Essential Downstream Effector Of Msx2supporting
confidence: 50%
“…In contrast to these studies, some investigators have demonstrated that BMPs negatively regulates the formation of endodermal progenitors (Poulain et al 2006;Sumi et al 2008). Sumi et al (2008) showed that BMP4 treatment does not induce the differentiation of human ES cells to mesendoderm/mesoderm progenitors. Moreover, Amita et al (2013) demonstrated that trophoblast is the predominant cell type which is derived from human ES cells in response to 10 ng/ml BMP4.…”
Section: Primitive Endoderm Specificationmentioning
confidence: 97%
“…A combination of BMP4 and activin A induces the differentiation of human ES cells first to definitive endoderm and then to pancreatic cells (Teo et al 2012). In contrast to these studies, some investigators have demonstrated that BMPs negatively regulates the formation of endodermal progenitors (Poulain et al 2006;Sumi et al 2008). Sumi et al (2008) showed that BMP4 treatment does not induce the differentiation of human ES cells to mesendoderm/mesoderm progenitors.…”
Section: Primitive Endoderm Specificationmentioning
confidence: 99%
“…Several published papers indicate the role of Wnt in supporting pluripotency [65,66], while other data emphasize Wnt signaling in hPSC differentiation [67]. Recently it has been suggested that different GSK3 pools may play different roles in the control of hPSCs fate determination [56].…”
Section: Q7mentioning
confidence: 99%